Does Job Fear God for Naught? - Ticciati, Susannah (Modern theology, 2005)
This article offers an interpretation of the book of Job which construes its principle agenda to be a tackling of the problem of obedience. Focusing on Job 9 and its legal terminology, it explores the dynamic of Job's integrity as that which emerges in the process of his wrestling with the law: while it transcends the law, it cannot exist apart from this process. From this a historical account of obedience is developed which can be reduced to neither act nor being.